JWST/NIRSpec Prospects on Transneptunian Objects - Métayer, Robin; Guilbert-Lepoutre, Aurélie; Ferruit, Pierre; Merlin, Frédéric; Holler, Bryan J.; Cabral, Nahuel; Quantin-Nataf, Cathy (Frontiers in Astronomy and Space Sciences, 2019)
The transneptunian region has proven to be a valuable probe to test models of the formation and evolution of the solar system. To further advance our current knowledge of these early stages requires an increased knowledge of the physical properties of Transneptunian Objects (TNOs). Colors and albedos have been the best way so far to classify and study the surface properties of a large number TNOs. However, they only provide a limited fraction of the compositional information, required for understanding the physical and chemical processes to which these objects have been exposed since their formation. This can be better achieved by near-infrared (NIR) spectroscopy, since water ice, hydrocarbons and nitrile compounds display diagnostic absorption bands in this wavelength range. Visible and NIR spectra taken from ground-based facilities have been observed for ∼80 objects so far, covering the full range of spectral types: from neutral to extremely red with respect to the Sun, featureless to volatile-bearing and volatile-dominated (Barkume et al. 2008; Guilbert et al. 2009; Barucci et al. 2011; Brown 2012). The largest TNOs are bright and thus allow for detailed and reliable spectroscopy: they exhibit complex surface compositions, including water ice, methane, ammonia and nitrogen. Smaller objects are more difficult to observe even from the largest telescopes in the world. In order to further constrain the inventory of volatiles and organics in the solar system, and understand the physical and chemical evolution of these bodies, high-quality NIR spectra of a larger sample of TNOs need to be observed. JWST/NIRSpec is expected to provide a substantial improvement in this regard, by increasing both the quality of observed spectra and the number of observed objects. In this paper, we review the current knowledge of TNO properties and provide diagnostics for using NIRSpec to constrain TNO surface compositions.